Penguatan Ketahanan Masyarakat terhadap Pandemi Covid-19 dengan Program Kuliah Kerja Nyata - Yuyun Estriyanto (DEDIKASI: Community Service Reports, 2020)
The Covid-19 pandemic is a problem that is being faced by the majority countries in the world. Various efforts have been made to reduce the spread of the virus, one of which is community service activities carried out by students or commonly referred to as Community Service Program (CSP). This article reports the CSP activities in the context of handling the Covid-19 pandemic carried out by a group of students in their home areas during the period of limiting learning activities on campus. The activity uses the community education method which consists of the stages of initial observation, program preparation, program implementation, and evaluation. The results of the evaluation show that the CSP program contributes to increasing public understanding of the Coronavirus, awareness to implement health protocols, productive economic activities, and online learning activities during the enactment of extraordinary conditions.